Penerapan Metode Net Present Value (NPV) Pada Kelayakan Investasi Syariah Waralaba Mixue di Indonesia - Adiwidya Muhammad Sofwan; Dendy Pramana Putra; Lukman Efendi (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2023)
International business development can be done in at least five ways, namely: 1. exporting, 2. through licensing, 3. franchising, 4. forming joint ventures, 5. total ownership, which can be done through direct ownership or acquisition. Net Present Value (NPV) is a net financial assessment that exists in the company after deducting other costs so that the value of the company's existing increase or lack of money can be used as a reference to assess the company's financial viability. The NPV method is carried out as a financial analysis of the feasibility of the Mixue franchise business, with the rise of the Mixue franchise present in Indonesia making an uproar and making conversations from buyers to entrepreneurs. Musharakah is a contract of cooperation between two or more parties for a business with profits and risks shared and all capital providers have the right to participate in management but are not required to do so.